Internet Users: Mysore University Campus (India) - Mulla, K. R.; Chandrashekara, M. (Journal of Information and Knowledge, 2006)
Investigators have made an attempt to explain the important aspects of Internet, the Internet being a computer network made up of thousands of networks worldwide. No one knows exactly how many computers are connected to the Internet. Internet and Internet based information resources are essential to overcome the distance barrier in information explosion, and it also saves the time, when searching the literature in electronic form and allows to identify the resources. Presently, Internet based information resources are increasingly used for various purposes. The teachers, research scholars and students of higher education use Internet to keep themselves up to date. The present study explains / gives an insight into why people are interested and what is their attitude towards the use of Internet based information resources and Internet use.